Application of Pathway Analysis Factors Affecting the Human Development Index in North Sumatra in 2021-2022 - Erwin; Balqis, Muthia Ferliani; Marpaung, Rony Genevent; Marpaung, J.L. (Journal of Mathematics Technology and Education, 2023)
The Human Development Index (IPM) measures human development achievements based on a number of basic quality of life components. As a measure of quality of life, HDI is built through a basic three-dimensional approach. These dimensions include a long and healthy life; knowledge, and a decent life. These three dimensions have a very broad meaning because they are related to many factors. To measure the health dimension, life expectancy at birth is used. Furthermore, to measure the dimensions of knowledge, a combination of literacy rate indicators and the average length of schooling is used. This study aims to determine the relationship or influence between variables on the human development index. These variables are the average length of schooling, life expectancy, and the percentage of poor people. This research uses survey data from BPS North Sumatra for the 2021-2022 period. Data processing uses path analysis with the help of SPSS version 23 software. The path equation obtained in this study is Y = 0.672X1 + 0.297X2 − 0.223Z + 0.081. The results showed that there was a significant influence between the average length of schooling, life expectancy, and the percentage of poor people on the human development index.